Computational and Empirical Investigation of Propeller Tip Vortex Cavitation Noise - Sezen, Savas; Bal, Sakir (SPRINGER MEDIZIN VERLAG GmBH, 2020)
In this study, non-cavitating and cavitating flow around the benchmark DTMB 4119 model propeller are solved using both viscous and potential based solvers. Cavitating and non-cavitating propeller radiated noises are then predicted by using a hybrid method in which RANS (Reynolds-averaged Navier-Stokes) and FWH (Ffowcs Williams Hawkings) equations are solved together in open water conditions. Sheet cavitation on the propeller blades is modelled by using a VOF (Volume of Fiuld) method equipped with Schnerr-Sauer cavitation model. Nevertheless, tip vortex cavitation noise is estimated by using two different semi-empirical techniques, namely Tip Vortex Index (TVI, based on potential flow theory) and Tip Vortex Contribution (TVC). As the reference distance between noise source and receiver is not defined in open water case for TVI technique, one of the outputs of this study is to propose a reference distance for TVI technique by coupling two semi-empirical techniques and ITTC distance normalization. At the defined distance, the starting point of the tip vortex cavitation is determined for different advance ratios and cavitation numbers using potential flow solver. Also, it is examined that whether the hybrid method and potential flow solver give the same noise results at the inception point of tip vortex cavitation. Results show that TVI method based on potential flow theory is reliable and can practically be used to replace the hybrid method (RANS with FWH approach) when tip vortex cavitation starts.
Keywords: FWH equation; propeller noise; tip vortex cavitation; TVI; TVC; CFD SIMULATIONS; PREDICTION; PERFORMANCE; SOUND; Engineering; Water Resources